2016
DOI: 10.1002/hbm.23179
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state functional connectivity of the human habenula in healthy individuals: Associations with subclinical depression

Abstract: Introduction The habenula (Hb) is postulated to play a critical role in reward and aversion processing across species, including humans, and has been increasingly implicated in depression. However, technical constraints have limited in vivo investigation of the human Hb, and its function remains poorly characterized. We sought to overcome these challenges by examining the whole-brain resting-state functional connectivity of the Hb and its possible relationship to depressive symptomatology using the high-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 110 publications
(169 reference statements)
16
101
0
Order By: Relevance
“…Therefore, the present findings could serve as a standard of the habenula functional connectivity at rest that could inform other works using less advanced instrumentation. A handful of recent studies have examined habenula resting state functional connectivity using standard 3-Tesla scanners (Ely et al, 2016; Erpelding et al, 2014; Hétu et al, 2016) while enhancing acquisition parameters to optimize spatial resolution (see in particular Hétu et al, although at the expense of field-of-view). Present findings replicate the habenula coupling with the relatively large regions of these previous reports; however, we also reveal connectivity previously only observed in animal work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the present findings could serve as a standard of the habenula functional connectivity at rest that could inform other works using less advanced instrumentation. A handful of recent studies have examined habenula resting state functional connectivity using standard 3-Tesla scanners (Ely et al, 2016; Erpelding et al, 2014; Hétu et al, 2016) while enhancing acquisition parameters to optimize spatial resolution (see in particular Hétu et al, although at the expense of field-of-view). Present findings replicate the habenula coupling with the relatively large regions of these previous reports; however, we also reveal connectivity previously only observed in animal work.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have revealed a number of connections. For example, one study reported resting state habenula connectivity with the ventral tegmental area (VTA), thalamus and sensorimotor cortex, as well as connectivity differences between subjects with low versus high subclinical depression (Ely et al, 2016). Another study acquired cardiac-gated functional images, revealing connectivity to subcortical areas such as the VTA and periaqueductal grey (PAG) (Hétu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Habenular asymmetry has been shown to be behaviorally important in vertebrates 41 . In humans, habenular RSFC has been shown to be asymmetric 42,43 . However, the functional significance of this asymmetry is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the habenula expresses nicotinic receptor alpha 5 subunit mRNA, which is absent in the thalamus 11 , and mu-opioid receptors 6 . Third, habenular resting state connectivity has been studied using a smaller voxel 42 , and the results are qualitatively very similar to ours: Although in this manuscript we focused only on the striatum and areas known or hypothesized to be important for the habenular reward-related circuit, high habenular connectivity with thalamus, anterior cingulate, posterior cingulate, superior frontal gyrus, and high "negative connectivity" with lingual gyrus and cuneus were observed both in the Ely manuscript and in our data (not shown). We believe that only a qualitative comparison between both sets of data should be done, since there are many differences between both manuscripts, including scanner, imaging parameters, data processing, and importantly sample characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…For signal outliers, the mean signal across the entire time series was computed and Z-transformed. Frames were classified as outliers if either the composite motion from the combination of translational and rotational displacements exceeded 2mm or the global mean signal exceeded 9 SD or both (Whitfield-Gabrieli and Nieto-Castanon, 2012; Ely et al, 2016). With this approach, the number of outlier volumes detected ranged from 0 to 4.6% of the total fcMRI volumes per participant.…”
Section: Methodsmentioning
confidence: 99%